The Improvement of Accreditation through Evaluation on Management Standards in Madrasah Tsanawiyah Al-Anwar Pontianak - Sukmawati Sukmawati; Yusak Ujang; Soeharto Soeharto (Universitas Negeri Makassar, 2019)
Accreditation preparations are carried out by the school prior to the visitation carried out by the assessor so that the results are less than optimal. The purpose of this study was to obtain information about the implementation of management standards through evaluation of the DISCREPANCY model at MTS Al-Anwar, North Pontianak. This research was a descriptive study and was conducted at MTs Al-Anwar. The research process is carried out in several stages, namely: the preliminary stage, pre-field, fieldwork, research, analysis of data collected findings, data presentation, and research reports. Data collection techniques used are direct communication techniques with data collection tools are interviews and direct observation techniques with a tool to collect data on observation and documentation format. Based on the research that has been done, the following results are obtained 1) The gap between expectations and reality on management standards; 2) Obstacles encountered in Madrasah Tsanawiyah Al-Anwar in implementing management standards, namely (a) The budget is not enough to carry out activities (RKAS) because the costs incurred are not in accordance with the plan; (b) There is no community assistance other than committee funds; (c) The number of education levels in one location has resulted in the development of madrasah tsanawiyah being hampered; (d) Adjacent to the Madrasah Tsanawiyah there are several schools around the place; 3) Efforts made by Madrasah to overcome obstacles through 1) Carry out activities in accordance with available funds; 2) The principle of openness to financial conditions to committees and teachers and staff; 3) There is BOS assistance and participating in the DNDMFN BOS, so that it can complement the needs of madrasah.